Is “Hit and Run” a Single Word? The Processing of Irreversible Binomials in Neglect Dyslexia - Arcara, Giorgio; Lacaita, Graziano; Mattaloni, Elisa; Passarini, Laura; Mondini, Sara; Benincà, Paola; Semenza, Carlo (Frontiers in Psychology, 2012)
The present study is the first neuropsychological investigation into the problem of the mental representation and processing of irreversible binomials, i.e. word pairs linked by a conjunction (e.g. ‘hit and run’, ‘dead or alive’). In order to test their lexical status, the phenomenon of neglect dyslexia is explored. People with left-sided neglect dyslexia show a clear lexical effect: they can read irreversible binomials better (i.e., by dropping the leftmost words less frequently) when their components are presented in their correct order. This may be taken as an indication that they treat these constructions as lexical, not decomposable, elements. This finding therefore constitutes strong evidence that irreversible binomials tend to be stored in the mental lexicon as a whole and that this whole form is preferably addressed in the retrieval process.